2021
DOI: 10.1002/syst.202000058
|View full text |Cite
|
Sign up to set email alerts
|

Iron‐Silicate Chemical Garden Morphology and Silicate Reactivity with Alpha‐Keto Acids

Abstract: Chemical gardens, which are self‐organizing, abiotic, inorganic precipitates in far‐from‐equilibrium systems, are of interest for prebiotic chemistry/origin of life research and, under certain reaction systems, can be considered hydrothermal vent analogs. While the presence of different additives to chemical gardens, including phosphate and amino acids, have been explored, the reactivity of organic molecules in chemical garden systems is not well understood. Here we explored the reactivity of two metabolically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…Classical experiments of 3D gardens grown from a seed are still carried out by many scholars and have produced a lot of important results. [68][69][70][71][72] Typically, the procedure involves placing a seed crystal of metal salt at the bottom of the vessel and filling it with solution. Thereafter, precipitation occurs around the seed and forms a semi-permeable membrane, and we will then observe tubular filaments just like the upward-growing tubes reported in this paper.…”
Section: Downward Finger Growthmentioning
confidence: 99%
“…Classical experiments of 3D gardens grown from a seed are still carried out by many scholars and have produced a lot of important results. [68][69][70][71][72] Typically, the procedure involves placing a seed crystal of metal salt at the bottom of the vessel and filling it with solution. Thereafter, precipitation occurs around the seed and forms a semi-permeable membrane, and we will then observe tubular filaments just like the upward-growing tubes reported in this paper.…”
Section: Downward Finger Growthmentioning
confidence: 99%
“…[1][2][3][4][5] For the past four centuries, numerous studies of these fascinating precipitation patterns have been reported. These studies focused on various physicochemical factors [6][7][8][9][10][11][12][13][14][15] including oscillatory growth of hollow microtubes, 12 tube growth with a pinned bubble, 14 and spiral growth of the tube controlled by the application of magnetic force. 15 Recently, chemical gardens have received attention as biomimetic materials due to their ability to form a variety of self-assembled structures, [16][17][18][19][20][21][22][23][24][25][26][27] such as silica-rich biomimetic mineral 20 and self-assembled nanostructures.…”
Section: Introductionmentioning
confidence: 99%